2021
DOI: 10.3390/jcm10132879
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Weight on Clinical Outcomes of Edoxaban Therapy in Atrial Fibrillation Patients Included in the ETNA-AF-Europe Registry

Abstract: Background: Extremes of body weight may alter exposure to non-vitamin K antagonist oral anticoagulants and thereby impact clinical outcomes. This ETNA-AF-Europe sub-analysis assessed 1-year outcomes in routine care patients with atrial fibrillation across a range of body weight groups treated with edoxaban. Methods: ETNA-AF-Europe is a multinational, multicentre, observational study conducted in 825 sites in 10 European countries. Overall, 1310, 5565, 4346 and 1446 enrolled patients were categorised into ≤60 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
(50 reference statements)
0
5
0
1
Order By: Relevance
“…Novel RCT evidence to address the use of DOACs compared with warfarin for stroke prophylaxis in AF patients with very low or very high BMI is unlikely given that many of the DOACs are nearing patent end. 20 Previous population-based studies have either included only a very small number of underweight patients, 21 only provided data for one DOAC, 22 or included venous thromboembolism as an indication for prescription. 21 …”
Section: Discussionmentioning
confidence: 99%
“…Novel RCT evidence to address the use of DOACs compared with warfarin for stroke prophylaxis in AF patients with very low or very high BMI is unlikely given that many of the DOACs are nearing patent end. 20 Previous population-based studies have either included only a very small number of underweight patients, 21 only provided data for one DOAC, 22 or included venous thromboembolism as an indication for prescription. 21 …”
Section: Discussionmentioning
confidence: 99%
“…In the post hoc analysis of the ETNA-AF-Europe trial evaluated 1-year outcomes in AF patients treated with edoxaban across a range of body weight groups, edoxaban seemed associated with a very low occurrence of stroke and bleeding, and there were no differences in the risks of stroke/SE (HR 1.14, 95% CI 0.48-2.71), major bleeding (HR 0.67, 95% CI 0.27-1.66), major or CRNM bleeding (HR 0.98, 95% CI 0.57-1.69), and intracranial hemorrhage (HR 0.93, 95% CI 0.17-5.10) among body weight groups after adjustment for eGFR and CHA2DS2-VASc score. 45 However, the morbid obesity cutoff point was >100 kg, which may not be extrapolated to patients with BMI >40 kg/m 2 or weight >120 kg.…”
Section: Resultsmentioning
confidence: 99%
“…After application of inclusion and exclusion criteria 29,135 patients formed the analytical cohort before matching (Supplementary Figure S2). Of those patients, 22 Fig. 1 shows that overall 78.3% of patients were prescribed warfarin, but initial prescription of warfarin declined during the study period from 95.7% in 2012 to 5.9% in 2018 with a concurrent increase in prescription of DOACs.…”
Section: Resultsmentioning
confidence: 99%
“…Novel RCT evidence to address the use of DOACs compared with warfarin for stroke prophylaxis in AF patients with very low or very high BMI is unlikely given that many of the DOACs are nearing patent end. 20 Previous population-based studies have either included only a very small number of underweight patients, 21 only provided data for one DOAC, 22 or included venous thromboembolism as an indication for prescription. 21 Observational studies conducted in the United States of America have found a similar or lower risk for stroke/ systemic embolism and major bleeding for apixaban, rivaroxaban and dabigatran compared with warfarin in obese cohorts.…”
Section: Articlesmentioning
confidence: 99%